How digital storytelling is used in mental health: A scoping review. (21st February 2016) - De Vecchi, Nadia; Kenny, Amanda; Dickson‐Swift, Virginia; Kidd, Susan
Abstract: The creative arts can be used to support stakeholders of mental health services to communicate and share their lived experience. Digital storytelling is one method that has been used to capture people's lived experience. In this scoping review, we were interested in mapping how digital storytelling has been used in mental health, and to identify gaps in the literature. Nine databases were searched to identify peer reviewed literature published between January 2000 and August 2015; 15 articles were included in the review. The articles were categorized across four broad areas: educational interventions, learning skills, learning about other people's lived experience, and learning about personal lived experience. We identify that while digital storytelling has potential as a participatory process to promote mutual understanding of and empathy towards lived experiences in mental health, there is a dearth of research in this area. More research is needed on the use of digital storytelling in mental health to determine its effectiveness in progressing a recovery orientation in service provision that is built on solidarity and a social justice agenda.